ANALYSIS OF EXCHANGE RATE STABILITY IN SUPPORTING SUSTAINABLE HEALTHY ECONOMIC GROWTH AND INCLUSIVE DURING COVID-19 IN THE FIVE DEVELOPED COUNTRIES - Pangeran Pangeran (Jurnal Ekonomi, 2023)
This study aims to analyze the contribution of variables from the interaction of Exchange Rate variables and Economic Growth. Where this study uses variables Export, Investment, and Interest Rates. This study uses secondary data or time series, namely from 2010 to 2020. The data analysis model in this study is the Simultaneous model, and the ARDL Panel and Different Tests. The results of the Simultaneous analysis show that the Export and Interest Rate variables are positive and have a significant effect while GDP is negative and has a significant effect on the Exchange Rate. The EXCHANGE variable is negative and has a significant effect on Economic Growth. Then the results of the ARDL Panel show that countries that are capable of becoming leading indicators for exchange rate stability are Japan, the United States, Singapore, Indonesia, and South Korea, this is because all the variables or indicators in the study namely (GDP, Exports, Investment, and SB) of these countries significant effect on the Exchange Rate. The results of the ARDL Panel Countries that are capable of becoming Leading indicators for stable Economic Growth are Japan, the United States, Singapore, and South Korea. Meanwhile, the State of Indonesia is unable to become a Leading indicator because all variables or indicators have no significant effect. The results of the Different Test show that there are no significant differences in Exchange Rates and GDP before and during the COVID-19 pandemic in 4 Developed Countries and 1 Country develop